Preclinical and clinical development of plant-made virus-like particle vaccine against avian H5N1 influenza. - Nathalie Landry (Public Library of Science (PLoS), 2010)
Unlabelled The recent swine H1N1 influenza outbreak demonstrated that egg-based vaccine manufacturing has an Achille's heel: its inability to provide a large number of doses quickly. Using a novel manufacturing platform based on transient expression of influenza surface glycoproteins in Nicotiana benthamiana, we have recently demonstrated that a candidate Virus-Like Particle (VLP) vaccine can be generated within 3 weeks of release of sequence information. Herein we report that alum-adjuvanted plant-made VLPs containing the hemagglutinin (HA) protein of H5N1 influenza (A/Indonesia/5/05) can induce cross-reactive antibodies in ferrets. Even low doses of this vaccine prevented pathology and reduced viral loads following heterotypic lethal challenge. We further report on safety and immunogenicity from a Phase I clinical study of the plant-made H5 VLP vaccine in healthy adults 18-60 years of age who received 2 doses 21 days apart of 5, 10 or 20 µg of alum-adjuvanted H5 VLP vaccine or placebo (alum). The vaccine was well tolerated at all doses. Adverse events (AE) were mild-to-moderate and self-limited. Pain at the injection site was the most frequent AE, reported in 70% of vaccinated subjects versus 50% of the placebo recipients. No allergic reactions were reported and the plant-made vaccine did not significantly increase the level of naturally occurring serum antibodies to plant-specific sugar moieties. The immunogenicity of the H5 VLP vaccine was evaluated by Hemagglutination-Inhibition (HI), Single Radial Hemolysis (SRH) and MicroNeutralisation (MN). Results from these three assays were highly correlated and showed similar trends across doses. There was a clear dose-response in all measures of immunogenicity and almost 96% of those in the higher dose groups (2 × 10 or 20 µg) mounted detectable MN responses. Evidence of striking cross-protection in ferrets combined with a good safety profile and promising immunogenicity in humans suggest that plant-based VLP vaccines should be further evaluated for use in pre-pandemic or pandemic situations. Trial registration ClinicalTrials.gov NCT00984945.